2008
DOI: 10.1016/j.bone.2007.12.224
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes, mechanosensing and Wnt signaling

Abstract: The majority of bone cell biology focuses on activity on the surface of the bone with little attention paid to the activity that occurs below the surface. However, with recent new discoveries, osteocytes, cells embedded within the mineralized matrix of bone, are becoming the target of intensive investigation. In this article, the distinctions between osteoblasts and their descendants, osteocytes, are reviewed. Osteoblasts are defined as cells that make bone matrix and osteocytes are thought to translate mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
760
1
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 918 publications
(815 citation statements)
references
References 117 publications
25
760
1
17
Order By: Relevance
“…Furthermore, DMP-1 expression levels were higher in the osteocytes of CXXC5 − / − mice (Supplementary Figure S3A, and Figures 3c and d). The number and length of osteocyte dendrites, which are essential for osteocytes to function as regulators of bone turnover and mechanosensors, 12 were also higher in CXXC5 − / − mice than in wild-type mice (Figures 3d-f, and Supplementary Figure S3B). Calcein double-labeling analyses 13 showed that bone formation by osteoblasts was accelerated in the femur of CXXC5 − / − mice (Figures 3g and h, and Supplementary Figures S3A and B).…”
Section: Cxxc5mentioning
confidence: 99%
“…Furthermore, DMP-1 expression levels were higher in the osteocytes of CXXC5 − / − mice (Supplementary Figure S3A, and Figures 3c and d). The number and length of osteocyte dendrites, which are essential for osteocytes to function as regulators of bone turnover and mechanosensors, 12 were also higher in CXXC5 − / − mice than in wild-type mice (Figures 3d-f, and Supplementary Figure S3B). Calcein double-labeling analyses 13 showed that bone formation by osteoblasts was accelerated in the femur of CXXC5 − / − mice (Figures 3g and h, and Supplementary Figures S3A and B).…”
Section: Cxxc5mentioning
confidence: 99%
“…[1][2][3] This network guarantees the supply of nutrition to distant osteocytes and allows the transit of small molecules and minerals that originate from the extracellular fluid. Furthermore, it enables direct intercellular communication among osteocytes, thus establishing an osteocyte network.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that osteocytes are mediators of mechanical and hormonal stimulations to control the activity of both osteoblasts and osteoclasts (1). Osteocytes are regulators of mineralization and mineral homeostasis (2,3), and by controlling Sost expression also act as modulators of Wnt signaling (4).…”
mentioning
confidence: 99%